PERAN PEMERINTAH DALAM MEMEBERIKAN PERLINDUNGAN TERHADAP TENAGA KERJA INDONESIA YANG BEKERJA DI LUAR NEGERI (Studi Pada Dinas Tenaga Kerja Dan Transmigrasi Provinsi Jawa Tengah ) - Dewi Trisnawati; Puji Astuti; Lusia Astrika (Journal of Politic and Government Studies, 2015)
AbstractThe lack of employment opportunities available in indonesia force indonesia citizens to work abroad. Indonesia workers who work overseas are mostly people who work in the non-formal sector and have limited protection. This is evidenced by the widespread cases of violence againt migrant workers, ranging from violence, rape, until the murder and no salary fulfilled labor during certain period of time. Depart from this, research raised the theme of the role of government in the protection of migrant workers working in foreign affairs and take the province of central java as the subject of research.The researchers in the study would be profound knowledge on how governments running the protection of indonesia migrant workers overseas. Because of thet, the method is applicable in a qualitative a descriptive.Based on the results of the study on the ground, protection is done by city administration through central java by such a process started from recruitment process in which also incude data and skills training, who collaborated with a placement service PPTKI and PJTKI, they stuble when migrant workers to solve the problem, the law of a country as well as the service which guarantees to ensure the safety of hometown. And to practice extortion and oppression against migrant workers aiready pretty much reduced because the enactment of KTKLN that facilitate the collection of migrant workers.Unfortunately, in the administration issued local regulation no further to describe the UU No. 39/2004, and in the future it published the regulation further to ensure security for their labor abroad. Given the sanction can only be imposed on not more varied PJTKI or PPTKI, it’s the illegal workers who dapart through that breach similar procedures should not happen again and monitoring of governmen guarantees could be more optimal.Said the key : of indonesia migrant workers, protection, the government